Diferencias departamentales del comercio intraindustrial colombiano con Estados Unidos y Latinoamérica - González Lozano, Bernardo (Editorial Uniagustiniana, 2020)
This chapter calculates the Grubel-Lloyd index based on information on exports and imports of colombian goods by tariff heading for bilateral trade relations between Antioquia, Atlántico, Bogotá, Caldas, Cundinamarca, Quindío, Risaralda, and Valle del Cauca (Colombia) with Argentina, Bolivia, Brazil, Chile, Ecuador, Mexico, Peru, Paraguay, Uruguay, Venezuela and the United States, for the 2011-2017 period. Key findings can be summarized as follows: i) differences in number of IIT (intra-industry trade) goods favor Antioquia, Bogotá and Valle; ii) existence of iit with both Latin American countries and the United States; and iii) differences in IIT patterns between the selected regions.